Security aspects of Philippine-China relations: Bilateral Issues and concerns in the Age of Global Terrorism - Banlaoi, Rommel C. (Manila, Philippines : Rex Book Store, 2007)
Since the signing of Memorandum of understanding between the Philippines and China on defense and security cooperation in May 2005, both countries already held three defense and security dialogues to date.
Chapter 1. Philippines-China Security: An introduction -- Chapter 2. Philippines-China Defense relations after 9/11 : Sustaining Friendship, enhancing cooperation. -- Chapter 3. Philippines-China Defense relations in the age of Terrorism ; Implications for Philippine National Security. -- Chapter 4. Philippines-China Defense and Military Cooperation: problems and prospects in the post 9/11 era. -- Chapter 5. Philippine Defense Policy -- Chapter 6. Southeast Asian perspectives on the Rise of China. -- Chapter 7. The ASEAN regional forum and the management of conflicts in the South China sea. -- Chapter 8. A Functional Approach to the management of Conflicts in the South China Sea. -- Chapter 9. The Philippines in China-US relations. -- Chapter 10. war on Terrorism in Southeast Asia : implications for the Philippine-China-US relations -- Chapter 11. Philippines-Taiwan security relations in the context of Philippine one-China policy : Current Situation and Future Trends.
Includes index.
Keywords: PHILIPPINES, CHINA RELATIONS